Evaluation of the Cost of Survivorship Care After Allogeneic Hematopoeitic Stem Cell Transplantation–An Analysis of 2 German Transplantation Centers - Wolff, Daniel; Bardak, Jelena; Edinger, Matthias; Klinger-Schindler, Ursula; Holler, Ernst; Lawitschka, Anita; Schoemans, Helene; Herr, Wolfgang; Kroeger, Nikolaus; Ayuk Ayuketang, Francis (Frontiers in Public Health, 2020)
The aim of the presented study was to analyze the care expenditure for outpatients after allogeneic hematopoietic stem cell transplantation (alloHSCT) done in accordance with the national, European guidelines and the German Social Law. We performed an analysis of the National and European survivorship care guidelines and in parallel recorded the time expenditure and staff costs separated according to different occupational groups involved in outpatient care at two German transplantation centers [University Hospital Regensburg (UKR) and University Hospital Hamburg-Eppendorf (UKE)]. In addition, we performed a comparison of real costs vs. reimbursed costs according to the standard rating benchmark catalog (EBM), which was supplemented by a survey of German transplantation centers. The results showed that the staff costs are only covered by the EBM for patients without complications during long-term follow-up care—notably, this accounts for 15% of alloHSCT patients. Staff costs for patients requiring treatment of graft-vs.-host disease or relapse of the malignant underlying malignancy exceed to the factor 6.5 (UKR) to 12 (UKE) of the EBM revenue, caused both by the increased duration and frequency of the outpatient visits. As a result of the survey at German transplant centers, 15 out of 18 responding centers reported a lack of cost coverage for follow-up care. Two/15 centers reported that survivorship care is limited to a restricted time, independent of patient's needs, due to a lack of cost reimbursement. The results show that alloHSCT survivorship care of patients requires significant staff resources, which are not covered by the current version of the German EBM catalog. New approaches to finance labor intensive after care of transplant patients are required.
CRIS-Team Scopus Importer:2023-03-23
Keywords: costs; Graft vs. Host disease; GvHD; haematopoietic stem cell transplant; re-imbursement; survivorship care model